STUDI KASUS: KONSEP DIRI PADA SISWA WITHDRAWAL - Nisa, Chairun; Astuti, Margaretha Tri; Garini, Natalia Ayu; Efita, Maini; Rahmayanty, Dinny (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Adolescence is a period when individuals begin to enter a wider social environment with the aim of searching for and forming their own identities. But not infrequently, individuals have not been able to adapt to the changing situations they face, giving rise to various obstacles. In individual development, one of the problems that is often faced is the behavior of withdrawing or being isolated from the social environment, also known as social withdrawal. This behavior is influenced by many factors, one of which is the self-concept that forms the basis of a person's behavior. This study aimed to describe self-concept in relation to student withdrawal. This study used a qualitative method with a descriptive type of case study. Data were collected through interviews, observation, and document study. One participant was identified as experiencing social withdrawal behavior - a teenager in grade X at Senior High School in Jambi City. Based on the research results, it is known that social self-concept influences how a person has social relationships. The subject's negative self-concept, such as being disturbing, unnecessary, and unpleasant, causes students to isolate themselves from their social environment and causes several symptoms, such as communication anxiety.